Polymer Graphite Pencil Lead as a Cheap Alternative for Classic Conductive SPM Probes - Knápek, Alexandr; Sobola, Dinara; Burda, Daniel; Daňhel, Aleš; Mousa, Marwan; Kolařík, Vladimír (Nanomaterials (Basel, Switzerland), 2019)
This paper presents polymer graphite (PG) as a novel material for the scanning tunneling microscopy (STM) probe. Conductive PG is a relatively modern nanocomposite material used for micro-pencil refills containing a polymer-based binding agent and graphite flakes. Its high conductivity and immunity against surface contamination, with a low price, make it seem like a highly suitable material for electrode manufacturing in general. For the tip production, three methods were developed and are further described in the paper. For the production, three commercially available polymer graphite rods were used. Each has been discussed in terms of performance within the tunneling microscope and within other potential applications.
Keywords: sharp tip formation; scanning tunneling microscopy; graphite